Perhitungan Jumlah Volume Tonase Batubara di PT Ansaf Inti Resources Kutai Kartanegara - Elok Aulia Noor Angelina; Ahmad Aris Mundir Sutaji; A. Arifin Itsnani SM; Radik Khairil Insanu (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
The purpose of this research is to explain the method of calculating coal volume using Gemcom Surpac 6.3 software. This research also aims to present the amount of coal tonnage in comparison to volume calculations for the period of November 2022. Calculating coal volume is crucial in determining the quantity of mineral deposits. This volume calculation is done as accurately and precisely as possible to produce accurate volume and tonnage. The method used in this research is net volume calculation (grid/borrow pit), where the excavation volume is the difference between cut and fill during a specific period. The data used in this research is secondary data. The results of this research are in the form of coal volume calculation and coal tonnage for one month of excavation in November 2022 using Gemcom Surpac software with the net volume method. From the calculation results, the coal volume is 139,309.26 tons, with each seam M being 66,116.02 tons, seam Q1 being 33,563.89 tons, and seam Q3 being 39,629.35 tons. For the density of newly excavated coal seams, it is 1.00, so it can be said that whatever the calculated coal volume using Gemcom Surpac software is the result of the tonnage itself. The result of coal volume calculation also has a standard deviation value of 1.96%. The calculation result does not exceed the standard deviation set by PT Ansaf Inti Resources, which is ≤ 3%